A CdTe/CdS quantum dots amplified graphene quantum dots anodic electrochemiluminescence platform and the application for ascorbic acid detection in fruits. (1st October 2015) - Chen, Hongjun; Li, Wang; Zhao, Peng; Nie, Zhou; Yao, Shouzhuo
Highlights: ECL properties of NGQDs were investigated. QDs induced ECL enhancement was discovered in homogenous solution. The enhancement is free of electrode modification. CdTe/CdS QDs enlarge 21-fold of the ECL intensity toward NGQDs. Applied for ascorbic acid detection in fruits. Abstract: Herein, a CdTe/CdS QDs (with a CdTe core and a CdS shell) amplified electrogenerated chemiluminescence (ECL) of nitrogen functional graphene quantum dots (NGQDs) platform is reported. The utilization of CdTe/CdS QDs could facilitate the production of NGQDs radical, and then, a high yield of NGQDs* was formed due to the interaction of NGQDs radical with O2 −, leading to an ∼21-fold ECL enhancement. This ECL enhancing system does not require the addition of coreactant and modification of electrode which is carried out in homogeneous solution. Benefiting from the remarkable ECL enhancement effect, a feasible and sensitive ECL sensor was constructed for ascorbic acid (AA) quantification. The proposed method features a detection limit of 70 nM with a linear calibration range from 100 nM to 100 μM, and exhibits good stability, practicability, and acceptable fabrication reproducibility, showing promising application in real-sample.